Logistics Performance Dimensions of Customs Clearance Efficiency and Export in ASEAN Economy - Anugrah Martua Raja; Marselina Djayasinga; Neli Aida (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
One of the dimensions of logistics performance is the efficiency of customs that evaluate the speed and ease of resolving customs affairs. It can be measured from service time and determined by human resources supported by internet utilization. This study analyzed the role of the efficiency of customs and export activities in supporting the economies of the Association of South East Asian Nations (ASEAN) by analyzing relevant variables such as export time, number of customs staff, internet users and export value. The research data used is secondary data from various sources starting from 2014 to 2019 which was analyzed with the Fixed Effect Model approach panel data regression method using E-Views 10. The results showed simultaneously export time, number of customs staff, internet users and export values had a significant effect on the ASEAN economy. Partially, the internet users and export values have a positive and significant effect while export time and the number of customs staff have a negative and significant effect. ASEAN governments should focus on accelerating the customs clearance process towards digitalization through application development by utilizing the internet rather than increasing the number of human resources to support exports and improve the ASEAN economy.